2012
DOI: 10.1177/0022343311427173
|View full text |Cite
|
Sign up to set email alerts
|

Climate variability, economic growth, and civil conflict

Abstract: Despite many claims by high-ranking policymakers and some scientists that climate change breeds violent conflict, the existing empirical literature has so far not been able to identify a systematic, causal relationship of this kind. This may either reflect de facto absence of such a relationship, or it may be the consequence of theoretical and methodological limitations of existing work. In this article we revisit the climate–conflict hypothesis along two lines. First, we concentrate on indirect effects of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 61 publications
2
110
0
1
Order By: Relevance
“…Can this non-finding be generalized to other continents or is the weak association between climatic anomalies and civil conflict primarily an Asian phenomenon? Although this study alone cannot offer a satisfactory answer, the results reported here are consistent with recent work on Sub-Saharan Africa that explicitly seeks to investigate plausible indirect effects (see Ciccone 2011;Koubi et al 2012;Theisen, Holtermann, and Buhaug 2011/12). At the same time, our main conclusion differs from some prominent studies that report a significant climate effect (Burke et al 2009;Hsiang, Meng, and Cane 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Can this non-finding be generalized to other continents or is the weak association between climatic anomalies and civil conflict primarily an Asian phenomenon? Although this study alone cannot offer a satisfactory answer, the results reported here are consistent with recent work on Sub-Saharan Africa that explicitly seeks to investigate plausible indirect effects (see Ciccone 2011;Koubi et al 2012;Theisen, Holtermann, and Buhaug 2011/12). At the same time, our main conclusion differs from some prominent studies that report a significant climate effect (Burke et al 2009;Hsiang, Meng, and Cane 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Existing literature indicates that the relation between interstate crises and energy natural resources remains rarely analyzed (Koubi et al, 2012). Due to the decrease of international armed conflict (Gleditsch and Pickering, 2014), I examine the impact of energy resources in international crises and move beyond an examination of the Militarized Interstate Dispute (MID) data (Ghosn et al, 2004).…”
Section: Crisis Initiationmentioning
confidence: 99%
“…Buhaug et al 2015;Caruso, Petrarca, and Ricciuti 2016;Koubi et al 2012;Schleussner et al 2016;Smith 2014;van Weezel 2015;Wischnath and Buhaug 2014). The literature is not short on proposed indirect links from climate change to conflict -among which intermediate implications for food insecurity, production shocks, and migration feature most prominently -but more research is needed along these lines before we are ready to conclude about the nature and strength of such connections.…”
Section: …But Impacts Of Climate Change Mightmentioning
confidence: 99%